Special Needs Parenting in Muslim Families during the COVID-19 Pandemic: A Mixed Method Approach - Asti Meiza Abdullah; Lufiana Harnany Utami; Hsiu-Shuo Hu (Faculty of Psychology, Sunan Gunung Djati Islamic State University of Bandung, 2023)
The COVID-19 pandemic worldwide has changed human life. The issue of education for children with special needs is increasingly difficult to implement during the pandemic. This study aims to obtain an overview of parenting styles during the COVID-19 pandemic for Indonesian Muslim families who have children with special needs. This research use a mixed method with a sequential explanatory approach where the quantitative method was followed by qualitative. Participants involved 18 families who have children with special needs. Data collection used the Parenting Scale which consists of 30 items. The results showed that most of the subjects experienced dysfunctional parenting with verbosity as the highest dysfunctional aspect. Qualitatively, the results lead to dysfunctional parenting. The pandemic period was indeed not easy to go through, especially for families who have children with special needs. This research shows that the challenging circumstances created by the pandemic can result in dysfunctional parenting. Parents should remain alert for signs of over-reactivity, verbosity, and looseness that can hinder effective parenting.